Assessment of transparent and reproducible research practices in the psychiatry literature. Issue 1 (12th February 2020) - Sherry, Caroline Elizabeth; Pollard, Jonathan Z; Tritz, Daniel; Carr, Branden K; Pierce, Aaron; Vassar, Matt
Abstract : Background: Reproducibility is a cornerstone of scientific advancement; however, many published works may lack the core components needed for study reproducibility. Aims: In this study, we evaluate the state of transparency and reproducibility in the field of psychiatry using specific indicators as proxies for these practices. Methods: An increasing number of publications have investigated indicators of reproducibility, including research by Harwicke et al, from which we based the methodology for our observational, cross-sectional study. From a random 5-year sample of 300 publications in PubMed-indexed psychiatry journals, two researchers extracted data in a duplicate, blinded fashion using a piloted Google form. The publications were examined for indicators of reproducibility and transparency, which included availability of: materials, data, protocol, analysis script, open-access, conflict of interest, funding and online preregistration. Results: This study ultimately evaluated 296 randomly-selected publications with a 3.20 median impact factor. Only 107 were available online. Most primary authors originated from USA, UK and the Netherlands. The top three publication types were cohort studies, surveys and clinical trials. Regarding indicators of reproducibility, 17 publications gave access to necessary materials, four provided in-depth protocol and one contained raw data required to reproduce the outcomes. One publication offered its analysis script on request; four provided a protocol availability statement. Only 107 publications were publicly available: 13 were registered in online repositories and four, ten and eight publications included their hypothesis, methods and analysis, respectively. Conflict of interest was addressed by 177 and reported by 31 publications. Of 185 publications with a funding statement, 153 publications were funded and 32 were unfunded. Conclusions: Currently, Psychiatry research has significant potential to improve adherence to reproducibility and transparency practices. Thus, this study presents a reference point for the state of reproducibility and transparency in Psychiatry literature. Future assessments are recommended to evaluate and encourage progress.